Islet-after-failed-pancreas and pancreas-after-failed islet transplantation: Two complementary rescue strategies to control diabetes. Issue 6 (19th February 2016) - Andres, Axel; Livingstone, Scott; Kin, Tatsuya; Campbell, Patricia M; Senior, Peter A; Kneteman, Norman M; Bigam, David; Shapiro, A M James
Abstract : For selected patients with type 1 diabetes, β-cell replacement is the treatment of choice, either by islet transplantation (ITX) or whole pancreas transplantation (PTX). When either modality fails, current practice is to consider retransplantation, or return to exogenous insulin. We investigate outcomes with PTX after failed ITX (PAI), and ITX after failed PTX (IAP). All patients receiving PAI or IAP at a single institution were identified. Donor and recipient variables were documented, including transplant outcomes analyzed for insulin requirement and metabolic control. Five subjects were listed for PAI, and 2 received transplants. Of the 4 listed for IAP, 3 have received transplants. The mean waitlist time was 4.5 ± 4.1 y for PAI and 0.35 ±0 .4 y for IAP (p = 0.08). Metabolic control was excellent after PAI, with 2/2 insulin-independent. After IAP, 1/2 achieved insulin independence and good metabolic control after 2 islet infusions. The third could not receive 2 nd infusion and presented c-peptide levels < 0.1 nmol/L. Both strategies are feasible. The outcomes after PAI in our center must be offset by much longer waitlist time due to the sensitization status of these patients. Data from multicentre experience will allow more robust comparative outcomes to be made, the current observations being restricted to a limited patient set.